Effect of genetic variants in cell adhesion pathways on the biochemical recurrence in prostate cancer patients with radical prostatectomy. (16th April 2019) - Yu, Chia‐Cheng; Chen, Lih‐Chyang; Lin, Victor C.; Huang, Chao‐Yuan; Cheng, Wei‐Chung; Hsieh, Ai‐Ru; Chang, Ta‐Yuan; Lu, Te‐Ling; Lee, Cheng‐Hsueh; Huang, Shu‐Pin; Bao, Bo‐Ying
Abstract: The aberrant expression of cell adhesion molecules is a hallmark of epithelial‐to‐mesenchymal transition, resulting in the transformation of cancer cells to a more aggressive phenotype. This study investigated the association between genetic variants in cell adhesion pathways and the prognosis of patients with prostate cancer following radical prostatectomy (RP). A total of 18 haplotype‐tagging single‐nucleotide polymorphisms (SNPs) in eight cancer‐related adhesion molecules were genotyped in 458 prostate cancer patients, followed by the replication of the top SNPs in an additional set of 185 patients. Log‐rank test and multivariate Cox regression analysis adjusted for covariates were used to evaluate associations with the risk of biochemical recurrence (BCR) after RP. In the discovery set, four SNPs in CDH2 were marginally associated with BCR. Among these, CDH2 rs643555C > T was found to be associated with BCR in the replication set. Patients with rs643555TT genotype had a significantly shorter BCR‐free survival compared with those with CC/CT genotypes in the combined analysis (adjusted hazard ratio 1.78, 95% confidence interval 1.19‐2.67, P  = 0.005). Additional analyses revealed that rs643555T was associated with higher expression of CDH2, and upregulated CDH2 was correlated with tumor aggressiveness and shortened BCR‐free survival. In conclusion, rs643555C > T affects CDH2 expression, and thus influences BCR in localized prostate cancer patients treated with RP. CDH2 rs643555 may be a promising biomarker to identify patients at high risk of poor prostate cancer prognosis. Abstract : This study assesses the associations of genetic variants in eight cell adhesion pathway genes with biochemical recurrence of patients with prostate cancer following radical prostatectomy. It was found that rs643555 affects the expression of CDH2, which in turn is correlated with tumor aggressiveness and patient prognosis.